Exploratory Investigation on the Influence of Machining Parameters on Surface Roughness and Tool Wear in the Turning Process of Steel ST-42 - Mubarok, Khamdi; Saputro, Agung; Mustajib, M Imron (International Journal of Science, Engineering, and Information Technology, 2023)
This study aims to investigate the influence of the conventional lathe machine's cutting parameters in the turning process of ST-42 steel material  on surface roughness and tool wear by employing an HSS tool. The examined cutting parameters encompass the spindle speed and the depth of cut, while maintaining a consistent feed rate. Each cutting parameter was evaluated at three different levels, spindle speed of 330 rpm, 360 rpm, and 500 rpm, and depth of cut 0.2 mm, 0.5 mm, and 1 mm, all with a uniform feed rate of 0.3 mm/minute. The findings of this research demonstrate that alterations in spindle speed and depth of cut exert a discernible influence on both surface roughness and tool wear. Elevated spindle speeds are associated with reduced surface roughness, albeit at the expense of increased tool wear. Conversely, deeper depth of cut correspond to heightened surface roughness, yet lead to decreased tool wear, aiming to achieve a uniform final diameter of the workpiece. By synergistic manipulation of these two parameters, the most favorable outcome in terms of surface roughness and tool wear can be identified. The lowest surface roughness was 4.42 μm, found at a spindle speed of 500 rpm coupled with the depth of cut of 0.2 mm. Meanwhile, the least amount of tool wear, quantified at 0.07 mm, was achieved at a spindle rotation speed of 330 rpm along with a cutting depth of 1 mm. The application of ANOVA analysis substantiates the statistical significance of both parameters, affirming their pivotal role in influencing surface roughness and tool wear.